Advances in systemic delivery of anti-cancer agents for the treatment of metastatic cancer - Grundy, M; Coussios, C; Carlisle, R (Taylor and Francis, 2016)
Introduction: The successful treatment of metastatic cancer is refractory to strategies employed to treat confined, primary lesions, such as surgical resection and radiation therapy, and thus must be addressed by systemic delivery of anti-cancer agents. Conventional systemically administered chemotherapeutics are often ineffective and come with severe dose-limiting toxicities. Areas covered: This review focuses on the recent developments in systemic therapy for metastatic cancer. Firstly, the strategies employed to improve the efficacy of conventional chemotherapeutics by ‘passively’ and ‘actively’ targeting them to tumors are discussed. Secondly, recent advances in the use of biologics to better target cancer and to instigate anti-tumor immunity are reviewed. Under the label of ‘biologics’, antibody-therapies, T cell engaging therapies, oncolytic virotherapies and cell-based therapies are examined and evaluated. Expert opinion: Improving specificity of action, and engaging the immune system appear to be key goals in the development of novel or reformulated anti-cancer agents for the treatment of metastatic cancer. One of the largest areas of opportunity in this field will be the identification of robust predictive biomarkers for use in conjunction with these agents. Treatment regimens that combine an agent to elicit an immune response (such as an oncolytic virus), and an agent to potentiate/mediate that immune response (such as immune checkpoint inhibitors) are predicted to be more effective than treatment with either agent alone.